2021
DOI: 10.3390/healthcare9060635
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Post-Traumatic Stress, and Burnout in Health Professionals during the COVID-19 Pandemic: Comparing Mental Health Professionals and Other Healthcare Workers

Abstract: The psychological impact of the pandemic on healthcare workers has been assessed worldwide, but there are limited data on how mental health professionals (MHPs) have been affected. Thus, this paper aims to investigate anxiety, post-traumatic stress, and burnout in a sample of MHPs. We conducted a descriptive, cross-sectional study on 167 participants: 56 MHPs, 57 physicians working closely with COVID-19 patients, and 54 physicians not working closely with such patients. MHPs reported good overall mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 59 publications
4
13
0
1
Order By: Relevance
“…On the other hand, this study identified a condition of well-being in users and staff in mental health care in Italy during COVID-19, which is in line with surveys conducted in Italy in the same era that found a condition of well-being in mental health workers [32,33]. The consistency of the good results from the other studies in Italy in terms of mental health during COVID-19 [32,33] can also support the generalizability of the Sardinian results to the Italian model, which, albeit with differences, is nevertheless unique in its specificity.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, this study identified a condition of well-being in users and staff in mental health care in Italy during COVID-19, which is in line with surveys conducted in Italy in the same era that found a condition of well-being in mental health workers [32,33]. The consistency of the good results from the other studies in Italy in terms of mental health during COVID-19 [32,33] can also support the generalizability of the Sardinian results to the Italian model, which, albeit with differences, is nevertheless unique in its specificity.…”
Section: Discussionsupporting
confidence: 87%
“…The pandemic has revealed the excessive optimism of these statements and has produced a shocking awareness in healthcare workers (HCWs) of the fragility and vulnerability of the Italian healthcare system ( 8 ). During the first months of the pandemic, a substantial number of health professionals found themselves without basic personal protective equipment, with scarce opportunities to get tested for the virus, and with the additional challenges of working in a system with considerable organizational deficiencies that soon went into crisis ( 9 13 ). In 2020, according to the Italian National Institute for Insurance against Accidents at Work, around 70% of over 100,000 work accidents claims due to COVID-19 were from HCWs, and 60% of the fatal cases concerned nurses ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of priority ranking, this study ranked psychological, biological and physiological risk management as the third, fourth and fifth management factors. Risk factors such as anxiety, irritability, sadness, bacteria, viruses, parasites and fatigue are of central importance in order to protect the occupational health of gas workers [ 2 , 4 , 47 ]. Various precautionary measures have been suggested in published literature [ 6 , 56 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, constant change in work conditions implies new workloads for workers [ 51 ]. Work overload destroys workers’ environment-coping competencies, which may produce emotional changes and symptoms of stress such as anxiety, irritability, sadness and depression, which is identified as a psychological and social risk factor [ 4 ]. More than that, chronic stress is likely to cause psychological stress and mental disorders [ 52 ].…”
Section: Literature Review and Conceptual Paradigmmentioning
confidence: 99%
See 1 more Smart Citation